The Impoliteness Strategies In Republican Party's DebateOf Donald Trump - Khurniawan, Rajid; , Agus Wijayanto, Ph.D; , Mauly Halwat Hikmat, Ph.D (2017)
Donald Trump is a US politician that has been successful using impoliteness strategies as a deadly weapon to win in US presidential debate. This research tried to investigate the impoliteness strategies used by Donald Trump and the most frequently strategies used by Donald Trump in GOP Debate Republican President election at Detroit when he faced Senator Marco Rubio, Senator Ted Cruz and Governor John Kasich. This research used descriptive qualitative as a method to cultivate the data. The researcher used impoliteness strategies from Culpeper(1996) to investigate Trump's impoliteness in GOP debate. The research findngs are as follows. There are frour impoliteness strategies used by Trump.They are bald on record, positive impoliteness, negative impoliteness and sarcasm. The total impoliteness strategies found is 100 data. Senator Marco Rubio is a candidate in debate stage that got the most frequently attack by Donald Trump. He was attacked by violating of the structure of conversation (17) data, condescend (2) data, ridicule (12) data, bald on record (1) data, call the other name (4) data, denied (6) data, disassociate from the other (4) data, use inappropriate identity markers (4) data and seek disagreement (5) data. The total, Trump attacked Senator Marco Rubio (55) time. It means 55% from the total of Trump's attack. From the data above it can be concluded that the impoliteness strategies used by Donald Trump in generally is as follows. There were ( 4) data 4%of bald on record. That was (1) data 1% of sarcasm. The positive impoliteness found consists of be disinterested (1) data 1%, disassociate from the other (8 ) data 8%, use inappropriate identity markers (5) data 5%, seek disagreement (5 ) data 5%, call the other name ( 6) data 6%, exclude the other from an activity (1) data 1%, denied (9) data 9%, and exclude the other from an activity (1) data 1%. The Total number of positive impoliteness found was (30) data 30%. The negative impoliteness that were found consist of ridicule (28)data 28%, explicitly associate the other with a negative aspect (1) data 1%, violate the structure of conversation (25) data 25%, condescend (3) data 3%, frighten (2) data 2%, be little (1) data 1%. The total number of negative impoliteness found is (60) data 60%. That was sarcasm 1 data 1%. The total impoliteness strategies found were (100) data 100%.The most frequently strategies used by Donald Trump is negative impoliteness.